Prenatal cannabinoid exposure: why expecting individuals should take a pregnancy pause from using cannabinoid products - Lin, Alexis; Dent, Gelonia L.; Davies, Suzy; Dominguez, Zarena M.; Cioffredi, Leigh-Anne; McLemore, Gabrielle L.; Maxwell, Jessie R. (Frontiers in Pediatrics, 2023)
Cannabinoid use in all populations is increasing as legalization across the United States continues.Concerningly, there is a lack of caution provided by medical providers to pregnant individuals as to the impact the use of cannabinoids could have on the developing fetus. Research continues in both the preclinical and clinical areas, and is severely needed, as the potency of delta-9tetrahydrocannabinol (THC), the primary psychoactive component of cannabis, has increased dramatically since the initial studies were completed. Thus far, clinical studies raise compelling evidence for short term memory deficits, impulse control issues, and attention deficiencies following prenatal cannabinoid exposure (PCE). These changes may be mediated through epigenetic modifications that not only impact the current offspring but could carry forward to future generations. While additional studies are needed, a pregnancy pause from cannabinoid products should be strongly recommended by providers to ensure the optimal health and wellbeing of our future generations.